Al-Quran in View of Theology Kalam Maturidiah and Shi'ah - Wijayanti, Tri Yuliana; Marlion, Ferki Ahmad; Irwandi, Irwandi; Marlion, Farid Ahmad (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Al-Qur'an is the holy book from Allah to the Prophet Muhammad and as proof of his prophethood. In Islam, the science that discusses the problem of divinity is studied in the science of kalam, which in its development emerged several theologies with different understandings, including Maturidiyah and Shi'ism. This study tries to find Maturidiyah and Shia views on the Qur'an. By using theological and textual approaches, the researcher explores the views of the two schools of thought on the Qur'an. Based on the results of the deductive analysis, it is concluded that Maturidiyah Samarkand distinguishes the kalam lafdzi and nafsiy of the Qur'an. This is because the Qur'an is an arrangement of letters and sounds, so it is lafdzi while nafsiy is an abstract word and cannot be detected through the human senses. Maturidiyah Bukhara views the Qur'an as not kalamullah (the nature of God), but kalamullah in the majazi sense. The Shia have a different view, namely the belief that the Qur'an in today's era is fake and not mutawatir. It is hoped that through this paper, it can increase people's faith in Allah swt and expand knowledge related to currents in the science of kalam. Al-Qur'an adalah kitab suci dari Allah kepada Nabi Muhammad saw sekaligus sebagai bukti kenabiannya. Dalam Islam, ilmu yang membahas masalah ketuhanan dipelajari dalam ilmu kalam, yang dalam perkembangannya muncul beberapa teologi dengan pemahaman yang berbeda-beda, di antaranya Maturidiyah dan Syi'ah. Kajian ini mencoba menemukan pandangan Maturidiyah dan Syiah terhadap Al-Qur'an. Dengan menggunakan pendekatan teologis dan tekstual, peneliti menggali pandangan kedua mazhab tersebut terhadap al-Qur'an. Berdasarkan hasil analisis deduktif, disimpulkan bahwa Maturidiyah Samarkand membedakan kalam lafdzi dan nafsiy al-Qur'an. Hal ini karena Al-Qur'an merupakan susunan huruf dan bunyi, sehingga bersifat lafdzi sedangkan nafsiy merupakan kata yang abstrak dan tidak dapat dideteksi melalui indera manusia. Maturidiyah Bukhara memandang al-Qur'an bukan kalamullah (sifat Tuhan), melainkan kalamullah dalam pengertian majazi. Syi'ah memiliki pandangan yang berbeda, yaitu keyakinan bahwa Al-Qur'an di era sekarang ini palsu dan tidak mutawatir. Diharapkan melalui makalah ini dapat meningkatkan keimanan masyarakat kepada Allah swt dan memperluas pengetahuan terkait arus dalam ilmu kalam.